2023
DOI: 10.3389/fvets.2023.1147386
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiographic scoring systems for assessment of bone healing after tibial plateau leveling osteotomy in dogs

Abstract: IntroductionAccurate radiographic assessment of bone healing is vital in determining both clinical treatment and for assessing interventions aimed at the promotion of bone healing. Several scoring systems have been used to evaluate osteotomy changes following tibial plateau leveling osteotomy (TPLO). The goal of this study was to compare the ability of five radiographic scoring systems to identify changes in bone healing following TPLO over time (Aim I), and to evaluate the influence of limb positioning on TPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A recent study comparing three previously described systems (including the 5-point system used in the current study) and two novel systems for assessment of bone healing after TPLO, found that the Visual Analogue Score system was the most appropriate to identify smaller changes in bone healing; this system was a novel variation of the 5-point scoring system with the addition of a 100-point scale, where 0 was labeled as "no healing" and 100 as "completely healed." 20 Intra-or interobserver reliability was not measured, and the 10-point scoring system was not included, making it difficult to compare their results with the ones of the present study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A recent study comparing three previously described systems (including the 5-point system used in the current study) and two novel systems for assessment of bone healing after TPLO, found that the Visual Analogue Score system was the most appropriate to identify smaller changes in bone healing; this system was a novel variation of the 5-point scoring system with the addition of a 100-point scale, where 0 was labeled as "no healing" and 100 as "completely healed." 20 Intra-or interobserver reliability was not measured, and the 10-point scoring system was not included, making it difficult to compare their results with the ones of the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Osteotomy healing following TPLO has been evaluated in multiple studies, and a 5-point (0-4) scoring system evaluating osseous bridging is commonly utilized. [14][15][16][17][18][19][20] A 10-point (0-10) scoring system was later developed, specifically for evaluation of bone remodelling at the osteotomy site in standard TPLO radiographs and although it appeared to provide a more sensitive evaluation of osteotomy healing, inter-and intraobserver variability were not evaluated in this study. 18 Other scoring systems have been used and compared; however, there is currently no standardized scoring system for the evaluation of osteotomy healing in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation